2013
DOI: 10.15407/spqeo16.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Laser heating effect on Raman spectra of Si nanocrystals embedded into SiOx matrix

Abstract: Abstract. Influence of combined size confinement effect and effect of local laser heating on the first-order Raman spectrum of silicon nanocrystals embedded into SiO x matrix has been studied. Increase of the local temperature of Si nanocrystals caused by laser illumination with the power density up to 10 mW/m 2 was estimated from the ratio of the Stokes/anti-Stokes peak intensities. Almost linear dependence of nanocrystals local temperature on the power density of exciting radiation with a rate of 63.6 Km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…They correspond, respectively, to the (Mn–O) stretching vibration in the basal plane of the MnO 6 sheet and to the symmetric stretching vibration (Mn–O) of the MnO 6 groups . The broad peak between 900 and 1000 cm –1 corresponds to the superposition of three transverse optical phonons ∼2TO­(X), 2TO­(W), and 2TO­(L) of silicon. , We observed that the intensity of the bands associated to Si and TiO 2 decreases after the synthesis of MnO 2 nanoflakes, confirming the covering of TiO 2 NRs by this nanomaterial. XRD and Raman results show that the low temperature of the synthesis leads to amorphous MnO 2 nanoflakes.…”
Section: Resultssupporting
confidence: 59%
“…They correspond, respectively, to the (Mn–O) stretching vibration in the basal plane of the MnO 6 sheet and to the symmetric stretching vibration (Mn–O) of the MnO 6 groups . The broad peak between 900 and 1000 cm –1 corresponds to the superposition of three transverse optical phonons ∼2TO­(X), 2TO­(W), and 2TO­(L) of silicon. , We observed that the intensity of the bands associated to Si and TiO 2 decreases after the synthesis of MnO 2 nanoflakes, confirming the covering of TiO 2 NRs by this nanomaterial. XRD and Raman results show that the low temperature of the synthesis leads to amorphous MnO 2 nanoflakes.…”
Section: Resultssupporting
confidence: 59%
“…88 The effect of local laser heating in the Raman spectrum of Si nanocrystals was also confirmed by Nikolenko. 89 Confocal micro-Raman spectroscopy is used because of its increased optical and depth resolution. Sampling depth, especially in transparent materials, has a direct effect in lateral resolution.…”
Section: Sampling Factors Affecting Raman Measurementsmentioning
confidence: 99%
“…88 The effect of local laser heating in the Raman spectrum of Si nanocrystals was also confirmed by Nikolenko. 89…”
Section: Standards For Specific Raman Applicationsmentioning
confidence: 99%
“…However, the exact physical mechanism for this asymmetry is not explained in the literature beyond the phenomenological PCM model. Several studies have questioned the phonon confinement model, suggesting that the asymmetry could instead originate from laser heating [159][160][161][162][163][164], or Fano resonance [165][166][167][168].…”
Section: Motivationmentioning
confidence: 99%
“…Other studies challenged the assertion that the asymmetry is due to Fano resonance and contend that it is instead caused by inhomogeneous laser heating [159][160][161][162][163][164]. These studies hypothesize that due to the finite spot size of the laser and finite penetration depth, the probe laser creates large temperature gradients.…”
Section: Motivationmentioning
confidence: 99%